Hydration prevents chronic hyperglycaemic patients from neurological deterioration post‐ischaemic stroke. (23rd January 2018) - Lin, J.; Weng, Y.; Li, M.; Mo, Y.; Zhao, J.
Abstract : Objectives: To determine whether chronic hyperglycaemia predisposes patients to dehydration, which may promote neurological deterioration, and to investigate whether dehydration control improves functional outcome. Patients and Methods: This study included 355 patients hospitalized with acute ischaemic stroke and diabetes mellitus who fulfilled the glycaemic gap ≤0. We used the following cut‐offs: (i) no chronic hyperglycaemia (glycated haemoglobin A1c [HbA1c] < 7%) and (ii) chronic hyperglycaemia (HbA1c ≥ 7%). The chronic hyperglycaemic patients were randomly divided into the control group and the hydration group. Hydration therapy was only initiated in the hydration group. The blood urea nitrogen (BUN)/creatinine (Cr) ratio was used as an indicator of dehydration. Stroke severity on admission and discharge was assessed by means of National Institutes of Health Stroke Scale (NIHSS). Results: The mean baseline BUN/Cr ratios were higher in the control group and hydration group than in the no chronic hyperglycaemia group. The mean BUN/Cr ratio decreased from 91.22 ± 29.95 on the first day to 77.03 ± 18.23 on the third day ( P  <   .001) in the hydration group. On the third day after admission, there was no significant difference in the BUN/Cr ratio between the hydration group and the no chronic hyperglycaemia group ( P  =   .831). Moreover, neurological deterioration was highest in the control group (33.6%, 36/107), followed by the hydration group (10.5%, 11/105) and the no chronic hyperglycaemia group (5.6%, 8/143). Conclusions: Chronic hyperglycaemia was associated with the admission NIHSS score and neurological deterioration after excluding the effect of stress hyperglycaemia. Furthermore, hydration therapy may help prevent neurological deterioration.